Effect of Phosphoric Acid on the Self Etching Primer Bond Strength and its Relation to Oral Health Status - E Yassini; M Hedayati (Tehran University of Medical Sciences, 2005)
Self etching primers, due to ease of manipulation, have been extensively used in recent years. These self etching primers containing a relatively weak acid, may not provide an optimal bond strength. The purpose of the present in-vitro investigation was to evaluate the effects of 37% phosphoric acid application prior to applying self etching primers on composite bond strength. In this experimental study a total of 48 premolar and molar teeth, free of caries, filling, abrasion, crack or other dental defects were selected. The extracted teeth were immediately stored in physiologic serum and divided randomly into two equal groups (n=24).Each group was also divided into two subgroups of twelve teeth each as follows: Subgroup A: enamel was not acid-etched, subgroup B: enamel was acid-etched (group I).Subgroup C: dentin was not acid- etched, subgroup D: dentin was acid-etched (group II).In acid-conditioned groups, water rinsing was followed by the application of a bonding agent (Etch & Primer 3), however for non-acid-treated groups, just the bonding agent was used. Then composite resin blocks (1.5×2 mm and 2.5 mm in diameter) were formed and light cured at all directions for 40 seconds, following this the specimens were placed in an Instron universal testing machine to determine shear bond strength. The data were analyzed by t-test. Results showed that no statistically significant differences were between the mean values of etch and un-etch enamel (P=0.232), similarly those of etch and un-etch dentin (P=0.148). In this investigation we concluded that acidic components employed in self-etching primers were of weak type, but self-etching primers could be used without phosphoric acid conditioning.